2007
DOI: 10.1111/j.1600-6143.2006.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex and Varicella Zoster Viruses: Forgotten but Not Gone

Abstract: Herpesvirus infections are common complications of organ transplantation. The most frequent herpesvirus infections are caused by cytomegalovirus (CMV), herpes simplex (HSV) and varicella zoster (VZV). Despite expansion of the therapeutic armamentarium, HSV and VZV continue to cause morbidity and occasional mortality in transplant recipients. Here we review the incidence and risk factors for HSV and VZV disease, their clinical presentation, effects of newer immunosuppressive regimens and prophylaxis for HSV and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 73 publications
2
59
2
6
Order By: Relevance
“…Organ nakilli hastalarda primer VZV enfeksiyonu nadirken, herpes zoster bu hasta grubunda daha sıklıkla izlenmektedir. İmmün sistemi baskılanmış olan bu hastalarda VZV reaktivasyon riski normal popülasyona göre artmıştır (6). …”
Section: Discussionunclassified
“…Organ nakilli hastalarda primer VZV enfeksiyonu nadirken, herpes zoster bu hasta grubunda daha sıklıkla izlenmektedir. İmmün sistemi baskılanmış olan bu hastalarda VZV reaktivasyon riski normal popülasyona göre artmıştır (6). …”
Section: Discussionunclassified
“…Our results demonstrated a low prevalence of VZV infection in renal transplant recipients (3.51%) compared with other studies that reported a prevalence of 3% to 10%. 3,4 Previous studies showed that female sex was a risk factor for developing HZ in liver transplant recipients, but 63% renal transplant patients who developed VZV infection were male. 3 The frequency and intensity of VZV infection is associated with the intensity of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…In solid-organ transplant recipients, the incidence of reactivation is 10-to 100-fold higher than the general population, ranging from 1% to 12%. 3,4 The typical clinical presentation of zoster is a painful, localized, unilateral, vesicular rash involving ≤ 2 adjacent dermatomes. 2 The VZV is an important pathogen after renal transplant.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with severe primary or generalized varicella-zoster virus infection, and in rare patients with disseminated herpes simplex infection, the use of an antiviral agent, such as acyclovir, can be highly effective if started early in the course of infection. 49 Antimicrobial treatment should be reassessed daily for potential de-escalation to prevent the development of resistance, to reduce toxicity, costs, and the development of superinfection by other pathogenic or resistant organisms such as Candida species, Clostridium difficile or vancomycin-resistant Enterococcus faecium. However, in some cases 11 (Pseudomonas species, only susceptible to aminoglycosides; enterococcal endocarditis; Acinetobacter species susceptible only to polymyxins), it is recommended to continue with a specific combination of antimicrobials.…”
Section: Antibioticsmentioning
confidence: 99%